1999
DOI: 10.1037/0278-7393.25.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Age, testing at preferred or nonpreferred times (testing optimality), and false memory.

Abstract: Two experiments investigated whether age and testing at preferred (optimal) times of day or nonpreferred (nonoptimal) times affected the ability to select relevant from irrelevant but thematically related alternatives in a verbal false memory paradigm. A 3rd experiment pursued the same issues with a visual false memory paradigm. In all 3 experiments, younger adults (n = 195) correctly recalled studied items more often than older adults (n = 121), whereas the 2 age groups correctly recognized about the same num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
79
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 54 publications
(113 reference statements)
15
79
4
Order By: Relevance
“…The subjects who acquired information in the afternoon performed better, even though one-third of the sample consisted of subjects classified as morning types. A plausible explanation for this result is that most studies that show an interaction between chronotype and cognitive task time-of-day applied memory tests with a short interval between training and the test (13)(14)(15). Perhaps, previously consolidated Data are reported as mean ± SEM of performance (hits minus errors).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects who acquired information in the afternoon performed better, even though one-third of the sample consisted of subjects classified as morning types. A plausible explanation for this result is that most studies that show an interaction between chronotype and cognitive task time-of-day applied memory tests with a short interval between training and the test (13)(14)(15). Perhaps, previously consolidated Data are reported as mean ± SEM of performance (hits minus errors).…”
Section: Discussionmentioning
confidence: 99%
“…The subjects of these studies were mostly young, a population with a greater tendency to being afternoon types (13,14). In this case, it could be suggested that the better performance of individuals who trained in the afternoon was a result of a synchronic effect and not related to training time-of-day (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacoby, 1999). However, it is important to note that age differences in absolute levels of false recognition are not always obtained in the DRM paradigm, at least under standard conditions (see, e.g., Benjamin, 2001;Budson, Daffner, Desikan, & Schacter, 2000;Intons-Peterson, Rocchi, West, McLellan, & Hackney, 1999;Kensinger & Schacter, 1999). This outcome may indicate that monitoring processes are not necessarily impaired with aging, or that, under standard DRM conditions, having additional monitoring resources available does not necessarily help younger adults reduce false recognition.…”
Section: Aging and Illusory Recollectionmentioning
confidence: 99%
“…Indeed, compared to younger adults, similar rates of illusory recollection and similar length effects on source judgements and MCQ ratings have been observed in older adults (Gallo & Roediger, 2003; see also Meade & Roediger, 2006). In contrast, some studies have shown increased false recollection in older adults, particularly if they were tested under forced recall conditions (Meade & Roediger, 2006), with repeated testing conditions (Skinner & Fernandes, 2009), or at their non-optimal time of the day (Intons-Peterson, Rocchi, West, McClellan, & Hackney, 1999). Similarly, recent data using the think-out-loud procedure suggest that older adults might be more likely to report illusory recollection and misrecollect details associated with studied items to justify their "Remember" judgements compared to younger adults (Dehon & Lampinen, in preparation).…”
Section: Agementioning
confidence: 99%